The World Bank Group and the global food crisis : an evaluation of the World Bank Group response. (Independent evaluation studies., 2014)
The unanticipated spike in international food prices in 2007-08 hit many developing countries hard. International prices for food and other agricultural products increased by more than 100 percent between early 2007 and mid-2008. Prices for food cereals more than doubled; and those for rice doubled in the space of just a few months. The food price increases were particularly hard on the poor and near-poor in developing countries, many of whom spend a large share of their income on food and have limited means to cope with price shocks. An estimated 1.29 billion people in 2008 lived on less than.